Respon Fagositosis Leukosit Polimorf Babi (in vitro) Terhadap Streptoccocus equi Subsp. Zooepidemicus (PHAGOCYTIC RESPONSE OF SWINE POLYMORPH LEUCOCYTES (IN VITRO) TO STREPTOCCOCUS EQUI SUBSP. ZOOEPIDEMICUS) - Utama, Iwan Harjono; Girindra, Aisjah; Pasaribu, Fachriyan Hasmi; Wibawan, I Wayan Teguh; Setiawan, Endhie D.; Ashadi, Gatut; Rompis, Aida Louise Tenden (Jurnal Veteriner; Vol 1 No 1 (2000), 2016)
Respon Fagositosis Leukosit Polimorf Babi (in vitro) Terhadap Streptoccocus equi Subsp. Zooepidemicus (PHAGOCYTIC RESPONSE OF SWINE POLYMORPH LEUCOCYTES (IN VITRO) TO STREPTOCCOCUS EQUI SUBSP. ZOOEPIDEMICUS)
Keywords: Streptococcus equi subsp, zooepidemicus, fagositosis